Polacy w Kościele katolickim na Kaukazie Północnym - Bogolubow, Aleksander (Annales Missiologici Posnanienses, 2023)
The history of the Poles in the North Caucasus dates back to the turn of the 16th and 17th centuries, but the presence of Catholic priests in this region can only be spoken of at the beginning of the nineteenth century. At first Polish priests only made travels to the Caucasus, but later began to set up parishes to address the spiritual needs of the Poles exiled there. The pastoral activity of the priests was not limited to the sphere of the spirit, but also focused on material help. An important point of their activity was the construction of churches. They collected donations for this purpose themselves and were also constantly supported by the Russian authorities. They were not detracted in their endeavors by the repressions that followed in the wake of the Polish national uprisings or suspicion of proselytism.